Produksi dan Profil Metabolit Bunga Krisan (Chrysanthemum sp.) pada Intensitas Cahaya Lampu LED dengan Durasi Yang Berbeda - Utami, Ika Nur; Nurchayati, Yulita; Hastuti, Endah Dwi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
Chrysanthemum is a Short Day Plant (SDP) that will flower if the day length is less than 12 hours. Indonesian Chrysanthemum farmers provide additional light at night to maintain the Chrysanthemumâ€™s vegetative phase so obtained the stem length which accordance to the cut flower standard (Â±76 cm). In other side, Chrysanthemum flowers are known has contain metabolites product andÂ potentially useful. This study is purpose to determine the effect of differences in LED light intensity and light exposure duration on growth, flower production, and metabolites profile of chrysanthemum. The study used a RAL method 3x2 factorial pattern which is in the form of giving an additional light intensity of 0 W, 10 W and 20 W and an additional light exposure duration of 2 hrs and 4 hrs. The results showed that the combination of 20 W + 4 hrs is optimaly increases the stem length (96,2 cm) and flowers diameter (6,6 cm). The 20 W light intensity is optimally inhibits the flower initiation and increases the amount of flower. The most compounds produced by chrysanthemum are from fatty acid groups, then hydrocarbons, and diterpenes. The combination of 10 W + 4 hrs is an optimally increases flower metabolites production that produces the most compounds compared to other treatments.